Discovery and Facile Synthesis of a New Silicon Based Family as Efficient Hydrogen Evolution Reaction Catalysts: A Computational and Experimental Investigation of Metal Monosilicides. Issue 8 (29th January 2021) - He, Yuan; Wang, Tan‐Ling; Zhang, Man; Wang, Ta‐Wei; Wu, Li‐Fan; Zeng, Lingyong; Wang, Xiaopeng; Boubeche, Mebrouka; Wang, Shu; Yan, Kai; Lin, Shi‐Hsin; Luo, Huixia
Abstract: A new family of transition‐metal monosilicides (MSi, M = Ti, Mn, Fe, Ru, Ni, Pd, Co, and Rh) electrocatalysts with superior electrocatalytic performance of hydrogen evolution is reported, based on the computational and experimental results. It is proposed that these MSi can be synthesized within several minutes by adopting the arc‐melting method. The previously reported RuSi is not only fabricated more readily but eventually explored 8 MSi that can be good hydrogen evolution reaction catalysts. Silicides then can be another promising electrocatalysts family as carbides, wherein carbon has the same electronic configuration as silicon. All explored silicides electrodes exhibited low overpotentials (34–54 mV at 10 mA cm −2 ) with Tafel slopes from 23.6 to 32.3 mV dec −1, which are comparable to that of the commercial 20 wt% Pt/C (37 mV, 26.1 mV dec −1 ). First‐principles calculations demonstrated that the superior performance can be attributed to the high catalytic reactivity per site that can even function at high hydrogen coverages (≈100%) on multiple low surface energy facets. The work sheds light on a new class of electrocatalysts for hydrogen evolution, with earth‐abundant and inexpensive silicon‐based compounds. Abstract : A family of transition‐metal monosilicides (MSi, M = Ti, Mn, Fe, Ru, Ni, Pd, Co, and Rh) with Pt‐like electrocatalytic hydrogen evolution reaction performance is developed and investigated combining experiment and theory. Their superior performance may be attributed to the high catalytic reactivity per site that can even function at high hydrogen coverages (≈100%) on multiple low surface energy facets.